Effect of cardiopulmonary bypass on hemostasis in patients undergoing cardiac surgery (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
This study aimed to evaluate the hemostatic derangement in patients undergoing elective cardiac surgery using cardiopulmonary bypass. Total 55 patients of either sex, were divided into three groups: Group A (n=20): Patients selected for elective cardiac surgery without cardiopulmonary bypass; Group B (n=20): Patients who undergone cardiac surgery with cardiopulmonary bypass time 90 min in comparison to other population. Prolong cardiopulmonary bypass time associated with more hemostatic abnormalities and complications can be minimized by shortening the bypass time.